Watermarking Technique for Improved Management of Digital Medical Images. (2nd November 2015) - Tsai, Jer-Min; Chen, I-Te; Huang, Ying-Fong; Lin, Cheng-Che
Abstract: Although digital medical imaging can improve diagnostic accuracy, efficient data man- agement and protection of patient privacy are major concerns. For example, an inadvertently modified medical image or a disordered series of medical images such as successive images of a beating heart may result in a misdiagnosis. The optimal use of digital medical images should timely detection of medical events while minimizing misdiagnoses and pro- tecting patient privacy. Improved detection of abnormal medical events would also improve the safety of patient care delivery models. We use a watermarking technique to embed im- portable patient data such as identity (ID), serial number or region of interest in the back- ground of a medical image to ensure that the image is matched with the correct patient and to indicate its relationship to other images in a series. The proposed method can be used to embed information at JPEG compression ratios as high as 70%